2010
DOI: 10.1093/pubmed/fdq010
|View full text |Cite
|
Sign up to set email alerts
|

English language proficiency and lifetime mental health service utilization in a national representative sample of Asian Americans in the USA

Abstract: The public health implications for behavioral health include the need to educate health-care providers working with Asian Americans regarding the benefits derived from seeking services and making interpreter services available in a culturally sensitive environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 23 publications
2
45
1
Order By: Relevance
“…Certain demographic correlates were more frequently associated with service use: age, gender, education level, marital status, and insurance status. Across all immigrant groups, those more likely to use services were women (39,43,50,52,63,80,81); those with higher education levels (35,43,82); and those who were divorced, widowed, or separated (40,82). In general, service use was positively associated with age (35,40,52,63,80,83), although one study found a negative association (48).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Certain demographic correlates were more frequently associated with service use: age, gender, education level, marital status, and insurance status. Across all immigrant groups, those more likely to use services were women (39,43,50,52,63,80,81); those with higher education levels (35,43,82); and those who were divorced, widowed, or separated (40,82). In general, service use was positively associated with age (35,40,52,63,80,83), although one study found a negative association (48).…”
Section: Resultsmentioning
confidence: 99%
“…Having insurance was positively associated with service use in many studies (35,38,40,50,52). However, one study showed that private insurance had this effect, whereas public insurance did not (66), and another reported no relationship between insurance status and mental health service use (82). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Altinkaya (1995) notes that the lack of accessible English classes, interpreters, or translated material has the potential to create an underclass of refugees. A study of 2095 Asian and Pacific Islander participants identified the patient's lack of English language proficiency and the shortage of providers who spoke the language of the minority patient as major barriers to receiving mental health services (Kang, et al, 2010). In addition, a shortage of appropriate interpreters, long waits for an interpreter, using untrained interpreters, and not paying attention to nonverbal communication have also been found as barriers to seeking mental health services on the part of the immigrants and refugees, as well as providing them with the appropriate quality of care (Bauer.…”
Section: Lack Of Knowledge Of the Host Languagementioning
confidence: 99%